Women`s Status Upon the Intestate Sucession in Roman and Contemporary North Macedonian Law - Esin Kranli Bajram (JUSTICIA (international Journal of Legal Sciences), 2019)
Having in mind the fact that this paper’s subject of interest basicaly is the place of women upon the intestate succession in Roman Law, and in the function of one more attestation for the influence of the Roman Law over the all ranges of iusprivatum of the continental legal systems, the conclusion of this short review will be brought down to an attempt to see the similarities, as well as the differences between the solutions of the Roman Law and the ones in the Macedonian legislation. In addition, the paper shows the chronologically separate characteristics of the determination of the legal successors, which are appropriately characteristic for the three development stages through which the entire legal system of the grandiose Roman Empire passed. The presentation of the gradual development and the changes hereby occurred, which are conditioned by the modified social conditions, as well as the strong custom component influencing the system of intestate succession on the other hand, argumentatively show the indisputable strong connection between the still nonpareil Roman legal genius and the legal transplants into the modern continental legal systems. The general conclusion which can be easily made from this partial analysis of the Roman law1 succession system is that the influence of the Roman legal mind upon the creation of the modern succession systems is significantly striking in comparison to the modern tendencies for this area. Of course, this conclusion refers to the general principles and foundations which are taken into account upon the regulation of the intestate succession lines. However, looking from historical point of view, it seems that the succession law is an area which underwent most modification and derivations of the Roman law rules compared to the rest ius privatum.
Keywords: Women’s Status, Intestate, Succession, Roman, Law.